Pengaruh Struktur Kepemilikan, Leverage, dan Modal Intelektual terhadap Integritas Laporan Keuangan - Mauludina Aulia Putri; Tumirin Tumirin (Jurnal Simki Economic, 2026)
This study examines the effect of ownership structure, leverage, and intellectual capital on the integrity of financial statements of companies listed on the Indonesia Stock Exchange during 2023-2024. Using a quantitative explanatory approach, the study analyze secondary data from annual reports selected through purposive sampling. Multiple linear regression analysis with SPSS was applied, supported by descriptive statistics, classical assumption test, t-tests, F-tests, and the coefficient of determination to ensure model reliability. The results indicate that ownership structure and leverage do not significantly affect financial statement integrity, while intellectual capital has a positive and significant effect. Simultaneously, all independent variables significantly influence financial statement integrity, with the model demonstrating strong explanatory power. Although limited by a relatively short observation period and selected variables, this study provides empirical contributions to accounting literature and offers practical insights for management and investors in improving the quality of financial reporting.